THE USE OF FIGURATIVE LANGUAGE AND IMAGERY IN SONGS’ LYRICS - Gunawan Tambunsaribu; Bob Morison Sigalingging (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2024)
In literary works, most authors express their feelings by using figurative language in their writing. The languages used in literary works usually represent the explicit and implicit feelings and thoughts of their characters. Someone may use figurative language to create unique and aesthetic communication. This study aims to find out the use of figurative language and imagery found in the two songs from Bruno Mars’ album entitled "Talking to the Moon” and “It Will Rain”. This study uses a qualitative method with a descriptive approach. This research showed that figurative language and imagery found in Bruno Mars’ selected song lyrics represented the author’s feelings and expressions delivered indirectly. Based on research findings, the writer found some figurative language in Bruno Mars’ selected songs. The most figurative language used in the lyrics of Bruno Mars’ selected songs is “Hyperbole”. This is usually used to emphasize human expression. The writer used hyperbole to make the lyrics more interesting to the listeners. In conclusion, these two songs use many kinds of figurative language and imagery. In literature, a writer uses figurative language as a tool to express and emphasize the elements of feeling, emotion, and experiences of human beings. By using figurative language and imagery, the reader can understand and imagine the aim of the writer.